Fluctuations of Glaciar Esperanza Norte in the north Patagonian Andes of Argentina during the past 400 yr - Ruiz, Lucas Ernesto (2012)
The number of studies of Little Ice Age (LIA) glacier fluctuations in southern South America has increased in recent years but is largely biased towards sites in the south Patagonian Andes. In this paper we present a detailed record of length and areal fluctuations of Glaciar Esperanza Norte (GEN) in the north Patagonian Andes of Argentina during the past four centuries. The GEN record was reconstructed through the dendro-geomorphological dating of moraines and the analysis of satellite imagery, aerial photographs and documentary material complemented with extensive field surveys. The maximum LIA extent at GEN was associated with an outer moraine dated to the mid 17th century. At least 19 subsequent readvances or standstills evidenced by morainic ridges were identified inside the most extensive LIA moraine. The dating and spacing of these moraines and the additional information available indicate that the ice front retreated much more rapidly during the 20th century than during earlier centuries. Comparison with the record of LIA fluctuations of Glaciar Frías, an ice mass of similar characteristics located 110 km to the north of GEN, shows a similar pattern of recession over the past 400 yr. Both glacier records have the peak LIA event occurring roughly during the same interval (early-mid 17th century) and show a minor readvance during the 1970s, but there are still a few discrepancies in the dating of some inner moraines. These differences may be due to local, specific factors or associated with the inherent uncertainties in the dating of the moraines. The chronologies of GEN and Frías are among the most detailed currently available in Patagonia, but a larger number of study sites is needed to develop robust, regionally representative glacier chronologies. Detailed glaciological, geomorphological and meteorological data are also needed to understand the glacier-climate relationships in this region and develop reliable paleoclimatic reconstructions.